Increased antimicrobial resistance against azithromycin during COVID: role of irrational utilization - Tanwir, Sidra; Sabah, Arif; Khatoon, Ambrina; Afridi, Faisal Iqbal (Journal of the Pakistan Medical Association, 2024)
Objective: To assess the use of azithromycin during coronavirus disease-2019 pandemic and its impact on antimicrobial resistance in an urban setting. Method: The retrospective, cross-sectional study was conducted on two different data sets. The first data set was of inpatients (N = 300) during the first wave of COVID 19 i.e. January to December, 2020. Data was collected from tertiary care hospitals in Karachi between October 2021 and November 2022 after approval from the ethics review committee of Ziauddin University, Karachi. Drug utilisation evaluation was done using a structured and validated tool. The treatment protocols were evaluated by comparing against the coronavirus disease-2019 treatment protocol 2020 and the guidelines issued by the Medical Microbiology and Infectious Diseases Society of Pakistan. Second data set comprised of the consumption data (obtained from pharmacies for both inpatients and outpatients) as well as the antimicrobial resistance, (obtained from antibiogram collected from the microbiology departments of the participating hospitals). This data was taken for the period of three years i.e. 2019 (Pre-COVID) to 2021 (Post-first wave of COVID) to establish trends of both consumption and antibiotic resistance. Data was analysed using SPSS 20. Results: Of the 300 patients, 207(69%) were males and 93(31%) were females. There were 162(54%) adults with mean age 40.06±10.48 years, followed by 120(40%) geriatrics with mean age 70.37±6.94 years 18(6%) paediatrics with mean age 13.5±3.60 years. All patients were given Azithromycin empirically followed by culture sensitivity test in 21% cases only. Comparison with COVID treatment protocols revealed the non-compliance of just 3%. However, in case of Community Acquired Pneumonia (CAP), sinusitis, typhoid and urethritis, comparison with MMIDSP guidelines revealed non-compliance of 95%, 22%, 75% and 100% respectively. Moreover, in 11% of patients, it was administered for conditions not recommended by guidelines. Furthermore, the Antibiogram exhibited percent increase in resistance against azithromycin. Conclusion: Enhanced consumption and irrational use of azithromycin during the coronavirus disease-2019 pandemic most likely contributed to increase in antimicrobial resistance. Key Words: Azithromycin, COVID-19, Misuse, Consumption, Resistance.